Upaya Guru dalam Meningkatkan Keterampilan Sosial Siswa Selama Pembelajaran di Masa Pandemi (Survei pada Guru Kelas Tinggi di Kecamatan Tanjungkerta) - Ramdayani, Nurlaila; Hanifah, Nurdinah; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2021)
Education is one of the aspects affected by the Covid-19 pandemic. Learning is carried out at home both online and offline in accordance with government instructions. The purpose of this study was to determine the teacher's effort to improving social skills student on learning during the pandemic. This is because the aspect of social skills (related to attitudes) is quite difficult to see its development in learning activities during the pandemic. The research method used is a survey with 69 respondents from 213 elementary school teachers in Kecamatan Tanjungkerta. The results of the study show that teachers in Kecamatan Tanjungkerta understand the importance of habituation of social skills in social studies learning and every lesson. The teacher's efforts have a big influence on the habituation and improvement of students social skills in learning activities during the pandemic. This can be seen from the coefficient of determination of 62.4%, it’s meaning that the teacher's efforts have a major influence on students social skills. This research is expected to have implications for increasing teacher efforts to adapt learning to applicable rules and cooperate with students parents.